Opinions of Teacher Candidates on the Usage of Mobile Applications in the Multimedia Development Processes - Ozdamli, Fezile; Ercag, Erinc (International Journal of Interactive Mobile Technologies (iJIM), 2018)
In order that mobile applications can be employed successfully in education, the opinions of teachers for using these applications must be identified and improved. For these reasons, the purpose of this study is to identify the opinions of teacher candidates, who are teachers of the future, on the usage of mobile applications in the process of multimedia project development. This study which was conducted with the purpose of identifying the opinions of teacher candidates on usage of mobile applications in education as means of communication employed qualitative method. Results is that using mobile applications in multimedia project development process attracted the attention of students and ensured effective communication.